ANALISA KEAMANAN INTERNET MENGGUNAKAN NESSUS DAN ETHEREAL UNIVERSITAS PUTRA INDONESIA “YPTK” PADANG - Rizki Nurdin (Universitas Negeri Padang, 2017)
With the existence of this information will be easily obtained, the exchange of data that occurs in the virtual world will increase. In addition to the development of this technology, unwittingly evolved also crimes that occur in cyberspace that can harm users who access these sites, ranging from the delivery of viruses, spamming or other types of crime. So that institutions connected in an Internet network will be very vulnerable to network security at the institution. This is given that the productivity of an institution or company will depend on the performance of the network in it. Damage that occurs in a network will result in data exchange that occurs on the network will slow or even damage the network system. Therefore a mechanism that is used to analyze network security is required. Computer network security systems connected to the Internet must be planned and well understood in order to protect the resources within the network effectively. Keywords : Nessus and Ethereal, Internet Security